2022
DOI: 10.5144/0256-4947.2022.119
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic ketoacidosis in Saudi Arabia: factors precipitating initial admission and readmission

Abstract: BACKGROUND: Diabetic ketoacidosis (DKA) is one of the complications of diabetes mellitus (DM), primarily type 1 DM. To our knowledge, only one study explored DKA readmission rates in Saudi Arabia. OBJECTIVES: Identify and analyze precipitating factors for DKA admission and readmission. DESIGN: Medical record review. SETTING: Tertiary care center. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
1
2
0
1
Order By: Relevance
“…Clinical manifestation among patients with diabetic ketoacidosis this study, we found the majority of study participants were younger than 40 years, participants' mean age was 35.6 and half of the patients were males which is nearly similar to other studies(Agarwal et al, 2016;Alotaibi et al, 2022). Most of the patients in our study were type 1 DM in line with previous studies(Agarwal et al., 2016; Alotaibi et al, 2022; Ndebele and Naidoo, 2018), Our study found that 8.5% of newly diagnosed patients with DM for the first time among patients admitted to the hospital with DKA which was lower than 16%-20% in previous studies (Almalki et al, 2016; Alotaibi et al, 2022; Iddi et al, 2017).…”
supporting
confidence: 88%
“…Clinical manifestation among patients with diabetic ketoacidosis this study, we found the majority of study participants were younger than 40 years, participants' mean age was 35.6 and half of the patients were males which is nearly similar to other studies(Agarwal et al, 2016;Alotaibi et al, 2022). Most of the patients in our study were type 1 DM in line with previous studies(Agarwal et al., 2016; Alotaibi et al, 2022; Ndebele and Naidoo, 2018), Our study found that 8.5% of newly diagnosed patients with DM for the first time among patients admitted to the hospital with DKA which was lower than 16%-20% in previous studies (Almalki et al, 2016; Alotaibi et al, 2022; Iddi et al, 2017).…”
supporting
confidence: 88%
“…Several researchers reported higher DKA episodes among patients of Saudi nationality with rates exceeding 50%. 23 , 27 In this particular study, it was noted that although the number of DKA episodes was slightly higher among Saudis, the severity of the episodes was more pronounced in non-Saudis.…”
Section: Discussionmentioning
confidence: 62%
“…There are two forms of DM, type 1 diabetes mellitus, which is the absence of insulin due to loss of pancreatic β-cells by the immune process and (Diabetes-Mellitus) Type 2, characterized by insulin resistance (Caetano et al, 2022;Elhassan et al, 2022). Saudi Arabia ranks among higher countries with an incidence of DM (Alotaibi et al, 2022). A common complication in a patient with DM is DKA, which frequently occurs at the beginning of T1DM diagnosis due to inadequate adherence to insulin treatment (Rakshit, 2021).…”
Section: Introductionmentioning
confidence: 99%